The United Nations Guiding Principles on Business and Human rights: A normative account of the business and human rights norm in the Malawian sugar industry - Murray, James Henry (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.